First polyallene-based well-defined amphiphilic diblock copolymer via RAFT polymerization. Issue 21 (24th May 2021) - Zhou, Mingtao; Wang, Shengfei; Ding, Aishun; Lu, Guolin; Huang, Xiaoyu; Jiang, Xue; Xu, Binbin
Abstract : We report the first well-defined amphiphilic diblock copolymer via allene and vinyl monomers. Abstract : Polyallenes containing internal double bonds directly attached to the backbone have attracted considerable attention due to their reactive structure and direct access to diverse functional polymers. Herein, we report the first example of controlled synthesis of polyallene-based diblock copolymers with tunable structure and low polydispersities via reversible addition–fragmentation chain transfer (RAFT) polymerization. RAFT homopolymerization of phenoxyallene (POA) was firstly conducted as a model reaction to explore the polymerization conditions. The preservation of end groups of the chain transfer agent (CTA) throughout the polymerization confirmed the livingness of poly(phenoxyallene) (PPOA). Next, well-defined poly( N -isopropyl acrylamide)- b -poly(phenoxyallene) (PNIPAM- b -PPOA) diblock copolymers were synthesized by RAFT block copolymerization of POA mediated by PNIPAM-based macroCTA. We demonstrate the in situ formation of unique nanofibers based on PNIPAM- b -PPOA diblock copolymer via polymerization-induced self-assembly (PISA) at high solid concentration in methanol. This work opens a new avenue to synthesize well-defined polyallene-based copolymers via living/controlled radical polymerization and nanoparticles for broad applications.